Prevalence of dementia and functionality in a geriatric clinic in Huancayo, Peru, 2016-2017 - Contreras, Coco (2019)
Introduction. Dementia is a public health problem; the World Health Organization promotes its research for the implementation of health policies against this disease. Objectives. To determine the prevalence of dementia and describe the functionality of older adults in a geriatric clinic in Huancayo, Peru. Methods. Observational and cross-sectional study, in a random probabilistic sample of 382 patients. Results The average age was 82,6 years, 60,7% was female, the primary education level was 49,7%, the place of origin Huancayo was 29,6%. The prevalence of dementia was estimated in 9,9%, mild cognitive deterioration in 11%. In basic activities of daily life, 19,4% had partial dependence; and in instrumental activities of life, 23% severe dependence. Conclusions. The prevalence of dementia in the sample studied was 9,9%, of mild cognitive impairment 11%. Likewise, 19,4% showed partial dependence and 23% severe dependence.